PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE TERHADAP KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI KELAS X DI SMA SRIJAYA NEGARA PALEMBANG - Lisa Yuliana; Ikbal Barlian; Riswan Jaenudin (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This research entitled "The Influence of Cooperative Learning Model "Inside Outside Circle Type to the activeness of students class X on Economic subject in SMA Srijaya Negara Palembang". The problem formulation of the research is "whether there is influence of cooperative learning model Inside Outside Circle Type to the activeness of student sclass X on Economic subject in SMA Srijaya Negara Palembang”. This research is an experimental research which uses pre experiment with One Group Pretest-Postest Design method. The population of this research is all students of class X in SMA Srijaya Negara Palembang. The sample used is cluster random sampling. In this case, there are 30 students of X IIS selected. The data collection techniques that used is observation. The technique of observation data analysis is obtained from the result of pre observation and post observation. The results of observational data analysis of learning models is 93.3% while the observation on learning activenessis. 79.1%. From the result, it can be interpreted that the students of class X IIS 1 areactive in learning. Furthermore, the hypothesis uses t test. The result of the research is t = 26,32 where, tcount> ttable = 26,32>1,685. This shows that there is influence of cooperative learning model "Inside Outside CircleType "to the activeness of student sclass X on Economic subject in SMA Srijaya Negara Palembang.